ELM suppression in helium plasmas with 3D magnetic fields. (21st June 2017) - Evans, T.E.; Loarte, A.; Orlov, D.M.; Grierson, B.A.; Knölker, M.M.; Lyons, B.C.; Cui, L.; Gohil, P.; Groebner, R.J.; Moyer, R.A.; Nazikian, R.; Osborne, T.H.; et al.
Abstract: Experiments in DIII-D, using non-axisymmetric magnetic perturbation fields in high-purity low toroidal rotation, 4 He plasmas have resulted in Type-I edge localized mode (ELM) suppression and mitigation. Suppression is obtained in plasmas with zero net input torque near the L–H power threshold using either electron cyclotron resonant heating (ECRH) or balanced co- and counter- I p neutral beam injection (NBI) resulting in conditions equivalent to those expected in ITER's non-active operating phase. In low-power ECRH H-modes, periods with uncontrolled density and impurity radiation excursions are prevented by applying n   =  3 non-axisymmetric magnetic perturbation fields. ELM suppression results from a reduction and an outward shift of the electron pressure gradient peak compared to that in the high-power ELMing phase. The change in the electron pressure gradient peak is primarily due to a drop in the pedestal temperature rather than the pedestal density.